Representasi Lingkungan dalam Serat Tata Cara: Analisis Leksikon Flora dan Fauna - Fadillah, Arif (Sutasoma : Jurnal Sastra Jawa, 2021)
The survival of the flora and fauna lexicon shows the environmental conditions of an era. This study aims to describe the survivalof the flora and fauna lexicon in the fiber of procedures and to describe the relationship of flora and fauna to the Javanese people.The method used in this research is the library method. This research is a qualitative descriptive research. This method includescollecting library data, reading research materials, recording and processing research data. The data from this research is the FiberProcedures obtained from the Ministry of Education and Culture repository. The results of this study are (1) the discovery of twocategories of words, namely in the form of nouns and numerals in the Fiber Procedures chapter of Wilujengan Meteng, (2) knowingthe level of survival of the flora and fauna lexicon, (3) knowing the relationship between flora and fauna for the Javanesecommunity in the form of natural relationships. human habitation which is the same as the habitat of flora and fauna. Throughthis research, it can be seen the survival of the flora and fauna lexicon in the fiber of procedures. Keywords: Fiber Procedures; lexicon; flora and fauna; Javanese society